2021
DOI: 10.3390/microorganisms9122414
|View full text |Cite
|
Sign up to set email alerts
|

A Mycobacteriophage-Based Vaccine Platform: SARS-CoV-2 Antigen Expression and Display

Abstract: The explosion of SARS-CoV-2 infections in 2020 prompted a flurry of activity in vaccine development and exploration of various vaccine platforms, some well-established and some new. Phage-based vaccines were described previously, and we explored the possibility of using mycobacteriophages as a platform for displaying antigens of SARS-CoV-2 or other infectious agents. The potential advantages of using mycobacteriophages are that a large and diverse variety of them have been described and genomically characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…It seems likely that there are a multitude of systems contributing to this, including both core bacterial functions and those provided by prophages and plasmids. There are additional genetic tools that could be developed from the phages including in vivo and in vitro packaging systems, vector systems including those using plasmidial prophage origins of replication [ 45 ], and phage-based vaccine systems [ 130 ]. The therapeutic potential of mycobacteriophages is also in its infancy, and it remains to be seen whether they will prove useful only as treatments of last resort, or whether they are more generally useful.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that there are a multitude of systems contributing to this, including both core bacterial functions and those provided by prophages and plasmids. There are additional genetic tools that could be developed from the phages including in vivo and in vitro packaging systems, vector systems including those using plasmidial prophage origins of replication [ 45 ], and phage-based vaccine systems [ 130 ]. The therapeutic potential of mycobacteriophages is also in its infancy, and it remains to be seen whether they will prove useful only as treatments of last resort, or whether they are more generally useful.…”
Section: Discussionmentioning
confidence: 99%
“…A noninfectious phage T4-CoV-2 vaccine with no tropism to human cells and no use of adjuvants or chemical stimulants represent significant advantages. Two recent phage-COVID vaccine studies using filamentous AAVP ( 71 ) and Bxb1 phage ( 24 ) also demonstrated the advantages of phage vaccine system, including the low cost of production, the self-adjuvanted nature, and the strong safety profile. In fact, our previous studies showed that adding adjuvants such as alum or liposomes did not further enhance the levels of immune responses ( 20 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protective immunity of the T4-CoV-2 nanovaccine could potentially be because of the repetitive and symmetrical arrays of S-trimers on phage particles, resembling the PAMPs (pathogen-associated molecular patterns) present on human viral pathogens ( 23 26 ). This architecture might mimic, in some respects, the spikes displayed on the SARS-CoV-2 virion ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great variation, 95% of them are non-enveloped, dsDNA, tailed phages [ 30 ]. In the majority of vaccine development cases, the capsid of dsDNA-tailed phages is used to express a viral antigen or a portion of an antigen, most typically via non-covalent linkages [ 31 ]. The concern of a significant reduction in the efficacy of existing COVID-19 vaccines due to rapid viral mutations could be resolved by the development of phage vaccines, such as phage displayed vaccines, phage DNA vaccines, and hybrid vaccines [ 32 ].…”
Section: Phages: An Ideal Platform To Design Multiplex Vaccinesmentioning
confidence: 99%